2022
DOI: 10.3390/ijms23116314
|View full text |Cite
|
Sign up to set email alerts
|

Design, Spectroscopy, and Assessment of Cholinesterase Inhibition and Antimicrobial Activities of Novel Coumarin–Thiadiazole Hybrids

Abstract: A novel series of coumarin–thiadiazole hybrids, derived from substituted coumarin-3-carboxylic acids was isolated and fully characterized with the use of a number of spectroscopic techniques and XRD crystallography. Several of the novel compounds showed intensive fluorescence in the visible region, comparable to that of known coumarin-based fluorescence standards. Moreover, the new compounds were tested as potential antineurodegenerative agents via their ability to act as acetylcholinesterase (AChE) and butyry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Moderate inhibition of cholinesterase enzyme (AChE and BuChE) was observed by compound 11 compared to standard (tacrine). It was concluded that the rigid structure of the compound was responsible for preventing them to adopt the necessary conformation for docking in enzyme binding site [37]. In 2021, a similar research group reported new analogues 12 of coumarin-thiadiazole and their corresponding Zn(II) and Cu(II) complexes and evaluated them for in-vitro Alzheimer's activity, concluding that substituting with amide group increases the inhibition of cholinesterase enzyme [38] (Figure 2).…”
Section: Anti-alzheimer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate inhibition of cholinesterase enzyme (AChE and BuChE) was observed by compound 11 compared to standard (tacrine). It was concluded that the rigid structure of the compound was responsible for preventing them to adopt the necessary conformation for docking in enzyme binding site [37]. In 2021, a similar research group reported new analogues 12 of coumarin-thiadiazole and their corresponding Zn(II) and Cu(II) complexes and evaluated them for in-vitro Alzheimer's activity, concluding that substituting with amide group increases the inhibition of cholinesterase enzyme [38] (Figure 2).…”
Section: Anti-alzheimer Agentsmentioning
confidence: 99%
“…Karcz D et al synthesized novel coumarin-thiadiazole derivatives, and tested the synthesized compounds for in-vitro anti-fungal and anti-bacterial activity. It was observed that only one compound 40 inhibited bacterial growth moderately, when compared to standard [37]. Pan N et al designed and synthesized twenty new pyrimidine analogues containing 1,3,4-thiadiazole ring.…”
Section: Anti-microbial Agentsmentioning
confidence: 99%
“…The existing therapy for AD involves the use of substances with structural similarities as the substrate neurotransmitters to interact with the cholinesterases and reduce catalytic activity. , However, there are reports of non-responders and side effects for the existing drug therapy, and more research into natural sources with high potency and low side effects is required. Although research in secondary metabolites from plant sources is very popular, the use of peptides as cholinesterase inhibitors is still in its infancy. Howbeit, the exploitation of the bioactive properties of peptides for the prevention and amelioration of physiological conditions, like hypertension, diabetes, and high cholesterol, is widely reported. Following this research trend, the structural and bioactive properties of cholinesterase peptide inhibitors derived from food proteins are currently being explored. , However, information is scant on the role of amino acid type and the positional arrangement of cholinesterase inhibition potency.…”
Section: Introductionmentioning
confidence: 99%
“…They obtained weak but promising inhibition from these compounds. [20] Onar et al, investigated the enzyme activities of coumarinÀ chalcone derivatives against acetylcholinesterase, α-glycosidase, and carbonic anhydrase. Most chalconeÀ coumarin derivatives was reported to have much better inhibition values than the reference compound acetazolamide for carbonic anhydrase.…”
Section: Introductionmentioning
confidence: 99%
“…Karcz et al ., synthesized coumarin−thiadiazole hybrids and their Cu(II) and Zn(II) metal complexes and tested them as acetylcholinesterase inhibitors. They obtained weak but promising inhibition from these compounds [20] . Onar et al ., investigated the enzyme activities of coumarin−chalcone derivatives against acetylcholinesterase, α‐glycosidase, and carbonic anhydrase.…”
Section: Introductionmentioning
confidence: 99%